Self‐Control Moderates Decision‐Making Behavior When Minimizing Losses versus Maximizing Gains. (23rd September 2014) - Pang, Bo; Otto, A. Ross; Worthy, Darrell A.
Abstract We examined (1) whether people would be more responsive to the delayed consequences of their decisions when attempting to minimize losses than when attempting to maximize gains in a history‐dependent decision‐making task and (2) how trait self‐control would moderate such an effect. In two experiments, participants performed a dynamic decision‐making task where they chose one of two options on each trial. The increasing option always gave a smaller immediate reward but caused future rewards for both options to increase. The decreasing option always gave a larger immediate reward but caused future rewards for both options to decrease. In Experiment 1 where the two options had equivalent expected value in the long run, participants were more prone to select the increasing option, which yielded larger benefits on future trials, in the loss‐minimization condition than in the gain‐maximization condition. Trait self‐control moderated the effect of losses by enhancing the effect for low self‐control participants while attenuating it for high self‐control participants. In Experiment 2 where selecting the increasing option was suboptimal, low self‐control participants still attempted to reduce losses on future trials by selecting the increasing option more often than high self‐control participants. These results suggest that decision makers value delayed consequences of their actions more in a losses domain relative to a gains domain and low self‐control individuals are more susceptible to such an effect. Copyright © 2014 John Wiley & Sons, Ltd.